Sistema de saúde no controle da sífilis na perspectiva das enfermeiras [Health system in syphilis control, from the nurses’ perspective] [Sistema de salud en el control de la sífilis en la perspectiva de las enfermeras] - Caroline Soares Nobre; Conceição de Maria de Albuquerque; Mirna Albuquerque Frota; Maria de Fátima Antero Sousa Machado; Camila Santos do Couto (Revista Enfermagem UERJ, 2018)
Objective: to learn the nurses’ perspective regarding the health system in syphilis control. Method:this qualitative study involved semi-structured interviews of thirteen nurses from a secondary, syphilis-referral hospital in Fortaleza, Ceará, in 2012. The content analysis technique was used to interpret the resulting corpus. Results: in the core themes identified, the salient categories were: Primary care is “failing” and “There is a flaw in health education!” Conclusion: it is believed that new resources and actions are needed for health professionals, coming mainly from educational interventions focusing on comprehensive health care so as to establish means to improve services.